Indonesian as the Language of ASEAN During the New Life Behavior Change 2021 - Wardhana, Dian Eka Chandra (Journal of Social Work and Science Education, 2020)
Indonesian is studied and used as a language in ASEAN because Indonesian is the lingua franca. In WordPress posts, the Indonesian language ranks third after English and Spanish. However, the attitude of native Indonesian speakers is still negative, so the Indonesian language UN scores (30% do not pass) are lower than the English national examination scores (only 5% do not pass). The purpose of this research is to describe the tendency of using Indonesian in ASEAN. The research data is in the form of information about the use of Indonesian in ASEAN. The data were collected online from members of 5 (international) communities, such as MLI, KSLI (alumni), AMCCA, and lecturers who had assisted students during internships through SEA teachers, SEAMEO, and youth exchanges with partner universities. This research data analysis using the Delphi technique and inter-subjectivity test. The findings are based on the panelist reliability test with a value of 0.7441 greater than 0.70, it is concluded that the model is consistent. Besides, the model reliability test was also carried out, and the result was that the value of r11 = 0.874 was greater than 0.70, so the model was reliable. The tendency in the use of Indonesian in ASEAN carries native speakers of conditioning results (nurture nativism) with the tendency as mentioned above is valid and reliable.